Reduction of Silver Ions by Cell Free Extracts of Westiellopsis sp. - Lakshmi, P. T. V.; Priyanka, Devi; Annamalai, A. (International Journal of Biomaterials, 2015)
Biosynthesis of silver nanoparticles using Westiellopsis sp. (A15), a filamentous cyanobacterium belonging to the family Fischerellaceae, has been demonstrated. Aqueous silver ions (Ag+) when exposed to the culture filtrate of Westiellopsis were reduced in the solution, which were characterized by biophysical measures utilizing the UV-Vis spectroscopy, scanning electron microscopy (SEM), and FTIR. The nanoparticles exhibited the maximum absorbance at 420 nm in UV-Vis spectroscopy, while the SEM micrograph revealed that the aggregated nanoparticles vary in size between 20 nm and 5 µm. However, the FTIR analysis provided evidence for presence of proteins in the filtrate to be involved in the reduction of silver ions.